Dynamical X‐ray diffraction imaging of voids in dislocation‐free high‐purity germanium single crystals. Issue 4 (12th June 2020) - Gradwohl, Kevin-P.; Danilewsky, Andreas N.; Roder, Melissa; Schmidbauer, Martin; Janicskó-Csáthy, József; Gybin, Alexander; Abrosimov, Nikolay; Sumathi, R. Radhakrishnan
Abstract : White beam X‐ray topography has been performed to provide direct evidence of micro‐voids in dislocation‐free high‐purity germanium single crystals. A general method is proposed to verify the presence of voids for any crystalline material of high structural perfection. Abstract : White‐beam X‐ray topography has been performed to provide direct evidence of micro‐voids in dislocation‐free high‐purity germanium single crystals. The voids are visible because of a dynamical diffraction contrast. It is shown that voids occur only in dislocation‐free parts of the crystal and do not show up in regions with homogeneous and moderate dislocation density. It is further suggested that the voids originate from clustering of vacancies during the growth process. A general method is proposed to verify the presence of voids for any crystalline material of high structural perfection.